STRATEGI PEMBELAJARAN PROBLEM BASED LEARNING DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR KOGNITIF PADA MATAKULIAH ILMU KEALAMAN DASAR - Dedy Ariyanto (Bioilmi: Jurnal Pendidikan, 2017)
The Science Subjects have an important influence for human life. The research is designed using quasi-experimental approach to the design of a simple 2 x 2 factorial. The research subjects was a university student of Special education . Students were selected in this study amounted to 55 students. The results of this study are: 1) the average value of the learning outcomes of students who are taught Sciences using Problem based learning is higher (at 4,500) of the learning outcomes of students who are taught Sciences using conventional models (at 1,241); 2) the average value of learning outcomes Sciences students have high motivation to learn at 3,250 while those with low motivation to learn at 2,296; 3) the experimental group students with high learn motivation have the best learning outcomes Sciences by 4,692 while the control group students with low learn motivation to learn science have the worst outcomes for 0,429. Based on the results of the study, the conclusions are : 1) Problem based learning model significantly influence learning outcomes, learning outcomes of Sciences subjects experimental group (tought using problem based learning model) is higher than in the control group outcomes study (taught using conventional model or lecture); 2) motivation to learn significantly affect learning outcomes, student learning outcomes Sciences high motivation to learn is better than the student learning outcomes that low motivation to learn; 3) there is no significant interaction between fine distinctions model of learning and fine distinctions motivation performed well in giving influence against student learning outcomes of Science.